An insight into zolpidem abuse and dependence - Świąder, Kinga; Szymańska, Ewa; Ostaszewska, Sandra; Augustynowicz, Kinga; Chrzanowski, Jakub; Łoginoff, Jan; Morawski, Przemysław; Popińska, Zuzanna; Pactwa, Filip (Journal of Education, Health and Sport, 2023)
Background: Z-drugs (zopiclone, zaleplon, and zolpidem) are commonly prescribed medicine classes associated with a risk of abuse, dependence or withdrawal. Objective: The purpose of our work is to review the current knowledge on the evidence for z-drugs harms and estimate the prevalence of dispensed prescriptions. Material and Methods: A literature review was conducted in PubMed database using the key words: “Zolpidem”, “Z-drugs”, “Abuse”, “Dependence” Results: According to our findings, zolpidem should be prescribed with the same caution as BZDs, especially in patients with a history of drug abuse or in the elderly. Conclusion: Psychiatrists and physicians should be aware of the misuse potential of zolpidem and adopt measures restricting its use.